Vibrating machinery theory, techniques and applications - Wen, Bangchun (Science Press ; Alpha Science International Ltd., 2012)
Theory, Techniques and Applications describes the working theory and techniques of vibrating machinery alongwith the applications, kinds, working principles and typical constructions of vibrating machines. This book describes the theories of several technical processes, the design and calculation methods of technical parameters, calculation and selection methods of the parameters of vibrating systems, the theories of vibratory synchronization and controlled synchronization of vibrating machines with dual- or multi-motor drives, the dynamic theories of linear and nonlinear vibrating machinery (including inertial vibrating machinery, flexible linkage vibrating machines and electromagnetic vibrating machines. Besides these some examples are introduced in this book. This book can be used by the students and graduate-students of the universities to be as the study and reference reader. And this book also can be used by the researchers and designers of the research institute and design enterprises.